2011
DOI: 10.1039/c0ce00681e
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic synthesis of M/Cu2O (M = Ag, Au) heterogeneous nanocrystals and their photocatalytic properties

Abstract: M/Cu 2 O (M ¼ Ag, Au) heterogeneous nanocrystals are successfully prepared by depositing noble metal nanoparticles onto the surfaces of Cu 2 O octahedral nanocrystals through a simple photocatalytic process. The samples are characterized by means of X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM) and energy dispersive X-ray analysis (EDX). The influence of the light source and solution temperature on the deposition of noble metal (taking Ag a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
103
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(103 citation statements)
references
References 40 publications
(40 reference statements)
0
103
0
Order By: Relevance
“…Overall, the improvement in degradation rate of MB, RhB and their mixed aqueous solution relies on the synergistic effect of H 2 O 2 and the as prepared CuS catalysts. [34][35][36][37] A brief description of the reaction mechanism in this degradation process is described below. MR .…”
Section: Optical Properties and Bet Surface Areamentioning
confidence: 99%
“…Overall, the improvement in degradation rate of MB, RhB and their mixed aqueous solution relies on the synergistic effect of H 2 O 2 and the as prepared CuS catalysts. [34][35][36][37] A brief description of the reaction mechanism in this degradation process is described below. MR .…”
Section: Optical Properties and Bet Surface Areamentioning
confidence: 99%
“…53 These electrons and holes can be captured by H 2 O 2 molecules, so the formations of oxidants (eqn (1)- (4)) have taken place. It has been demonstrated that because of their high oxidative capacities, the photo-generated oxidant species are in favor of oxidizing organic contaminants.…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%
“…Because Cu 2 O nanocubes possess only one type of exposed crystal plane, noble-metal nanoparticles can be homogeneously deposited on the surfaces of Cu 2 O nanocubes. Compared with our previously reported Cu 2 OÀAu and Cu 2 OÀAg nanocomposites prepared through a photocatalytic technique, [30] the method described herein is more convenient and quick, and the deposition of Au and Ag nanoparticles on Cu 2 O is more uniform. The obtained Cu 2 OÀAu and Cu 2 OÀAg nanocomposites can serve as efficient SERS substrates.…”
Section: Introductionmentioning
confidence: 87%